Kinerja Pelayanan Air Bersih pada Perusahaan Umum Daerah Air Minum Ake Gaale Kota Ternate : Studi Kasus di Perumda Air Minum Ake Gaale Kota Ternate - Meti Mahdiati; Chairullah Amin; Rizal Teapon (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
The Ake Gaale Regional Drinking Water Company as a public service company definitely put ther customer interests as the main thing. Perumdam Ake Gaale is required to strive to improve its services. This research was conducted with the aim of measuring the service performance of the Perumdam Ake Gaale using the Data Envelopment Analysis (DEA) method and as using the number of customers, air loss rate, number of arrears and air usage as input and income as outputas parametrs. From the research results, it was found that only 17 of the 27 sub districts that were assessed as having a score below 1 (efficient) showed poor performance so that they had no influence on service efforts to increase the company's income.